A EKSPLORASI DAMAR KURUNG SEBAGAI KEARIFAN LOKAL KABUPATEN GRESIK: EKSPLORASI DAMAR KURUNG SEBAGAI KEARIFAN LOKAL KABUPATEN GRESIK - Rahmawati, Yeni; Wiryanto, Wiryanto; Mariana, Neni; Hendratno, Hendratno; Istiq’faroh, Nurul (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
Damar Kurung, a traditional lantern art from Gresik Regency, East Java, is a cultural symbol that is full of local wisdom values. This study aims to examine the cultural meaning, social role, and preservation efforts of Damar Kurung in Gresik society. Using a qualitative approach, this study involved interviews with artists, craftsmen, and community leaders, as well as direct observation of local cultural activities. The results of the study indicate that Damar Kurung is not only a work of art, but also a medium for conveying moral messages, history, and the collective identity of the community. This study examines Damar Kurung, a traditional lantern art from Gresik Regency, which has a deep meaning as a symbol of local wisdom. The purpose of the study is to explore the history, philosophical meaning, and relevance of Damar Kurung in the context of modern culture and its preservation efforts. The methodology used is a qualitative approach through in-depth interviews with local artists, direct observation of art exhibitions, and analysis of related literature. The results of the study indicate that Damar Kurung not only functions as a decorative element, but also as a medium of social expression that reflects the life of the Gresik community, togetherness, and traditional values. Despite the challenges of decreasing interest of the younger generation and the development of the times, preservation efforts with digital innovation and collaboration between communities, artists, and the government have shown promising results. These findings emphasize the importance of preserving Damar Kurung as a cultural heritage that has the potential to strengthen local identity and introduce Gresik's local wisdom to a wider audience